Comparison of Maseration and Sonication Method on Flavonoid Extraction from Mango Leaves: Effect of Solvent Ratio - Alifiana Permata Sari; Nur Layli Amanah; Awalia Wardatullathifah; Agung Nugroho (ASEAN Journal of Chemical Engineering, 2022)
Mango leaf extract has proven to contain flavonoids that serve as antioxidants. In this study, a comparison between traditional maceration and sonication on flavonoid extraction from mango leaf was investigated. The various ratios of ethanol and acetone were utilized as solvents (1:5, 1:10, and 1:15). The sonication process, which uses an ultrasonic cleaning bath set at 40 oC, takes 30 minutes as contrasted to the maceration procedure of 36 hours treatment at room temperature. The flavonoid test using aluminum (III) chloride (AlCl3) colorimetric technique shows that acetone provides greater solvent power than ethanol. According to this study, the optimal ratios for the maceration and sonication procedures are 1:10 and 1:15, respectively. The maceration process resulted in the optimum extract of 0.186 mgQE/g dry leaves. Meanwhile, using a 1:15 acetone solvent ratio and the sonication method, the highest concentration of flavonoid components was discovered, reaching 0.143 mgQE/g dry material with 54 times shorter time.